Erica Tietze-Conrat, Tagebücher Band III: Register - Caruso, Alexandra (2015)
In her early diaries the art historian Erica Tietze-Conrat discribes her eventfull life in Vienna in the 1920ies, were she had been in touch with all the important art circles of the time.. In 1937 and 1938 her journals give an interesting view of the networks between museumstafs, art dealers, art scholars and artists just before the outbreak of World War II.